Penerapan Workplace Stretching Exercise untuk Menurunkan Kelelahan Kerja pada Karyawan PT Intidragon Suryatama Kota Mojokerto - Dwiharini Puspitaningsih; Ika Suhartanti; Fitria Wahyu Ariyanti; Rahmi Syarifatun Abidah (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2026)
This community service program aims to reduce employee work fatigue through the implementation of a structured Workplace Stretching Exercise program in collaboration with PT Intidragon Suryatama, Mojokerto City. Employees and company management were actively involved as program partners (mitra kegiatan) in the planning, implementation, and evaluation stages to ensure program relevance and sustainability. The program was consisted of four stages: preparation, coordination with company management, implementation of educational and practical sessions, and evaluation of outcomes. A total of 44 employees participated in this activity. The intervention included health education regarding work fatigue, demonstration of 24 stretching movements, and guided practice sessions lasting 8–10 minutes performed routinely during work hours. Fatigue levels were measured using the Industrial Fatigue Research Committee (IFRC) subjective fatigue scale before and after the intervention. The results indicated a notable decrease in fatigue scores from 52.05 to 43.39, demonstrating an improvement in physical comfort, reduced muscle tension, and enhanced alertness during work. Accompanied by qualitative feedback indicating improved physical comfort, increased alertness, and higher awareness of occupational health and safety practices. Beyond physiological benefits, the program contributed to the development of a healthier work culture by integrating active breaks into daily routines. This program demonstrates that Workplace Stretching Exercises are practical, low-cost, easy to integrate into daily routines, and beneficial for employee health and well-being model of community-based occupational health promotion. The activity is recommended for continuous implementation as part of occupational health promotion efforts within the company.